Estudio comparativo de residuos de ditiocarbamatos en papa - Hernandez, R.=700 1 Suarez, P.; Castillo, S.
(Es, En)
Ilus., 11 ref.
Keywords: SOLANUM TUBEROSUM; RESIDUOS DE PLAGUICIDAS; FUNGICIDAS; DITIOCARBAMATO; MANCOZEB; METODOS; ESPECTROMETRIA; CUBA